EGFR Mutation-positive Lung Cancer in Real-world Treatment Outcomes: A Multicenter Study from Thailand - Sukauichai, Sitthi; Maneenil, Kulthida; Supavavej, Archara; Paul, Vinai; Benjawongsathien, Duangnapa; Chantharakhit, Chaichana; Neesanun, Sunee; Chayangsu, Chawalit; Bowornkitiwong, Thissawan; Sukaraphat, Napawan (Asian Pacific Journal of Cancer Care, 2022)
Background: Epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKI) have been the standard of care as first-line (1L) therapy for patients with advanced EGFR mutated lung cancer since 2009. In Thailand, however, it was not fully introduced to all health care funds until 2020. The purpose of this study was to determine the overall survival (OS) and treatment pattern in the period before EGFR-TKI became universally available to all patients. Methods: This was a retrospective study conducted at 10 medical centers in Thailand. Patients harboring the common mutation (exon 19 deletion or exon 21 L858R) diagnosed during January 2013 and December 2019 were enrolled. Results: This study included 284 patients with a median follow-up time of 19.8 months and a death rate of 80.3% (228/284). Clinical characteristics included median age 62.5 years, female 65.5%, never-smoking 74.3%, stage 3B/4/recurrence 2.1/93.3/4.6%, exon 19/exon 21- 60.9/38.7%. Treatment patterns to EGFR-TKI included not receiving (NR) (9.5%), first-line (1L) (56.0%), switch maintenance (MN) (3.5%), second-line (2L) (21.8%) and third-line (3L) or more (9.2%). Median OS of patient receiving EGFR-TKI as NR, 1L+MN, 2L and 3L or more was 11.10 (95%CI: 8.21 to14.00), 19.08 (95%CI: 15.76 to 22.41), 23.06 (95%CI: 15.91 to 30.21) and 32.46 (95%CI: 21.61 to 43.30) months (p=0.006), respectively. Factors contributing to poor prognosis in the multivariate model included poor ECOG-PS (HR 3.17, 95%CI: 1.96-5.13), not receiving EGFR-TKI (HR 3.83, 95%CI, 1.94-7.56) and receiving EGFR-TKI 1L (HR 2.30, 95%CI: 1.40-3.79) Conclusion: OS of patients with EGFR mutation positive lung cancer treated with EGFR-TKIs in Thailand was comparable to clinical studies. EGFR-TKI treatment should be provided to patients as early as possible, but TKI remained beneficial at later points in the treatment timeline.